Peatlands Are More Beneficial if Conserved and Restored than Drained for Monoculture Crops - Tarigan, Suria; Zamani, Neviaty P.; Buchori, Damayanti; Kinseng, Rilus; Suharnoto, Yuli; Siregar, Iskandar Z. (Frontiers in Environmental Science, 2021)
Peatlands are especially important but fragile tropical landscapes. The importance of peatlands is owing to their ability to 1) sequester a considerable amount of terrestrial carbon, 2) store freshwater, and 3) regulate floods during the rainy season. Nowadays, extensive peatland degradation occurs because of peatland utilization for agriculture purposes, causing severe environmental consequences such as carbon emission, loss of biodiversity, risk of flooding, and peat fire. Meanwhile, local planners and decision makers tend to overlook the long-term strategic function of peatlands for carbon storage and hydrological regulation, preferring peatland utilization for short-term economic benefits. The objective of our study is to quantify the total ecosystem services (except biodiversity) of a tropical peatland landscape in various peat-utilization scenarios to help build awareness among local planners and decision makers on the strategic tradeoff between peatland utilization and restoration. Studies on the total ecosystem services in a tropical peatland landscape involving hydrological regulation are still rare. Based on the net present value calculation, provisioning services, carbon regulation, and hydrological regulation in our study area account for 19, 70, and 11% of the total ecosystem services, respectively. Based on uncertainty analysis, at any combination of the social cost of carbon emission (within a range of USD 52.7–USD 107.4) and discount rate (within a range of 5–10%), the enrichment of peatlands with paludiculture crops (e.g., jelutong) shows superior ecosystem services compared to other peatland-utilization scenarios. Conversely, planting peatlands with monoculture crops, which are associated with peatland drainage, shows a rapid decrease in the total ecosystem services. The fluvial carbon export in our study, which is often neglected in a peatland carbon budget, increases the estimate of the total carbon budget by 8%. Restoring undrained peatlands with paludiculture crops such as jelutong contributes positively to carbon sequestration and potentially reduces carbon emissions by 11%. These quantitative findings can help local planners and decision makers in understanding the tradeoff between the long-term benefits of peatland restoration and the short-term economic benefits of peatland utilization for monoculture crops.